2018
DOI: 10.1037/adb0000388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features associated with an increased risk for alcohol use disorders among family members.

Abstract: This study evaluated the risk for alcohol use disorders (AUDs) among first-degree relatives depending on whether a specific family member (proband) had an AUD history. For probands with AUD histories, we also evaluated whether certain clinical features were associated with higher rates of AUDs in family members as a means for identifying markers that signify a more familial form of AUD. The proband sample was recruited from high schools in Western Oregon communities at Age 16 and followed longitudinally until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Of these, 490 (67%) families produced data on all first-degree relatives and 242 (33%) provided data on some members ( M = 62% of all first-degree relatives within families) but missing data on one or more members. As reported elsewhere (Farmer et al, 2018), no differences on proband AUD history status were observed as a function of missing family data although there were some demographic differences related to missingness in some comparisons. Overall, 2414 adult first-degree relatives (730 biological mothers, 719 biological fathers, 476 female siblings, 489 male siblings) contributed data to this research.…”
Section: Methodssupporting
confidence: 70%
“…Of these, 490 (67%) families produced data on all first-degree relatives and 242 (33%) provided data on some members ( M = 62% of all first-degree relatives within families) but missing data on one or more members. As reported elsewhere (Farmer et al, 2018), no differences on proband AUD history status were observed as a function of missing family data although there were some demographic differences related to missingness in some comparisons. Overall, 2414 adult first-degree relatives (730 biological mothers, 719 biological fathers, 476 female siblings, 489 male siblings) contributed data to this research.…”
Section: Methodssupporting
confidence: 70%
“…Furthermore, participants filled out a baseline DrInC-2R (Miller, 1995), a 40-item self-administered inventory that measures the adverse consequences of drinking, unconfounded with other dimensions-consumption patterns, help seeking, and dependence-by focusing on 5 areas: physical, interpersonal, intrapersonal, impulse control, and social responsibility. Additionally, the family (mother/father) history of alcohol problems was collected, as it has been shown to be an indicator of increased risk and severity of AUD (Farmer et al, 2018). Other alcohol-related clinical characteristics included in our analyses were the age of onset and duration of AD, as well as the total number of drinks, DPDD, HDD, and PDA in the 30 days prior to baseline.…”
Section: Sample Characteristicsmentioning
confidence: 99%